2015
DOI: 10.1016/j.pmedr.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wrist-worn activity monitor feedback on physical activity behavior: A randomized controlled trial in Finnish young men

Abstract: The purpose of this study is to evaluate whether the use of an activity monitor providing feedback has an effect on physical activity (PA) in young men. A population-based sample of 276 conscription-aged (mean = 17.9, SD = 0.7 years) men participated in a 3-month randomized controlled trial in Oulu in 2012. Participants were randomized to an intervention group (INT, N = 137) and a control group (CON, N = 139). INT received a wrist-worn monitor (Polar Active) showing daily activity, and CON received identical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 40 publications
0
100
0
Order By: Relevance
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table summarizes study characteristics, while Table S2 tabulates detailed study characteristics. Of the 51 included studies, 20 studies were eligible for meta‐analysis of BMI, 19 studies were eligible for meta‐analysis of weight, and 10 studies were eligible for meta‐analysis of waist circumference …”
Section: Resultsmentioning
confidence: 99%
“…Of the 51 included studies, a total of 43 measured change in weight, with 41 of these having an objective measure of weight and two using a self‐report measure for weight . This includes 19 studies from the meta‐analysis and a further 24 studies that reported weight as an outcome with results in a format that was not compatible for inclusion in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the epoch of interest, the MAD is calculated from the resultant of the three orthogonal accelerations and it describes the mean variation of the dynamic acceleration component around the static component. On the other hand, Polar Active represents wrist-worn accelerometer with high user-friendliness (Brugniaux et al, 2010; Schaefer et al, 2014; Troiano et al, 2014; Jauho et al, 2015). In earlier studies Polar Active has been found to relate to indirect calorimetry and double labeled water with regard to energy expenditure (EE) calculation (Brugniaux et al, 2010; Kinnunen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Association analysis was done to assure the importance of identified data-driven factors in 9 explaining different levels of PA intensity. The PA metrics were calculated using previously validated cut-points (SED, 1-1.99 MET; LPA, 2-3.49 MET; and MVPA, ≥ 3.5 MET) by the accelerometer manufacturer (28).…”
Section: Association Analysismentioning
confidence: 99%